2007
DOI: 10.1002/hep.1840030102
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by S-Adenosyl-L-Methionine of Hepatic Na+, K+-ATPase, Membrane Fluidity, and Bile Flow in Rats with Ethinyl Estradiol-Induced Cholestasis

Abstract: Structural and functional changes in the surface membranes of hepatocytes play a pivotal role in the induction and reversion of some forms of drug-induced cholestasis. To elucidate the mechanism by which S-adenosyl-L-methionine (SAMe) leads to a partial reversion of bile flow impairment caused by ethinyl estradiol (EE), female Sprague-Dawley rats were given oral doses of EE (5 mg per kg per day, for 3 days) with and without simultaneous administration of SAMe (26 mg per kg, 3 times per day, for 3 days). Na',K'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(19 citation statements)
references
References 31 publications
2
16
0
1
Order By: Relevance
“…They observed that EE treatment significantly reduced the activity of Na + , K + -ATPase, accompanied by the diminishment of bile flow, and that canalicular Na + , K + -ATPase activity was significantly correlated with bile flow. These observations were confirmed by several subsequent studies [130][131][132], supporting an important role of Na + , K + -ATPase activity in the regulation of bile flow by EE [130][131][132][133]. In contrast to EE, E2 was found to stimulate Na + , K + -ATPase activity.…”
Section: Na + -K + -Atpase As a Target Of Estrogens And Estrogen-likesupporting
confidence: 70%
See 1 more Smart Citation
“…They observed that EE treatment significantly reduced the activity of Na + , K + -ATPase, accompanied by the diminishment of bile flow, and that canalicular Na + , K + -ATPase activity was significantly correlated with bile flow. These observations were confirmed by several subsequent studies [130][131][132], supporting an important role of Na + , K + -ATPase activity in the regulation of bile flow by EE [130][131][132][133]. In contrast to EE, E2 was found to stimulate Na + , K + -ATPase activity.…”
Section: Na + -K + -Atpase As a Target Of Estrogens And Estrogen-likesupporting
confidence: 70%
“…17b-estradiol (E2) and estrogen-like molecules, could be ligands of Na + , K + -ATPase. It has been known that the synthetic estrogen, ethinyl estradiol (EE), induced impairment of bile flow and bile salt maximum secretory function in rat liver and that the structural and functional changes in surface membranes of hepatocytes play a pivotal role in EE-induced cholestasis [130][131][132]. Reichen and Paumgartner [133] studied the relationship between bile flow and Na + , K + -ATPase in liver plasma membranes enriched in canaliculi in rats treated with EE.…”
Section: Na + -K + -Atpase As a Target Of Estrogens And Estrogen-likementioning
confidence: 99%
“…In some forms of liver diseases, the activity of (Na + , K + )-ATPase may be impaired as shown in an animal model of endotoxin-induced cholestasis (156). Also, treatment of rats with pharmacologic doses of ethinylestradiol has been found by some to reduce the activity of (Na + , K + )-ATPase (11,107) but not by others (17,18,95) 2. NTCP expression can be up or down regulated in certain forms of human liver diseases.…”
Section: Role Of Ntcp In Liver Function Testsmentioning
confidence: 99%
“…By altering function at the level of the hepatic surface membrane, SAMe improves the impairment of bile flow caused by increased levels of ethinyl estradiol. 69 Studies of SAMe in rats have shown reversal of cholestasis in those treated with ethinyl estradiol. 70 Several randomized studies examining SAMe have been performed in humans with ICP.…”
Section: Phenobarbitalmentioning
confidence: 99%